Has the Church of England lost the English people?: Some quantitative tests. Issue 2 (March 2017) - Field, Clive D.
Claims made by the authors of That Was the Church that Was (2016) that the Church of England has 'lost' the English people since 1986 are examined through religious statistics. Both attachment and attitudinal indicators are reviewed, the former showing the decline of the Church has been long-term, the latter that division between Church and nation is not always clear-cut.